Powers of Comptrollers to Request Bankruptcy Declaration for Commercial Companies and Judicial Oversight - boutosh, Ahmad; Balas, Hashim; Alsmadi, Mamoon Suliman (Journal of Ecohumanism, 2024)
The study aimed to outline the procedure for requesting the disclosure of insolvency applications by the Comptroller General of Companies, along with the conditions to be adhered to when filing such applications. Additionally, it explored the judicial oversight of the control powers exercised when submitting insolvency disclosure requests. Key findings of the study highlighted that the comptroller of companies derives the authority to submit insolvency notices from Article 193 of the Jordanian Companies Act. This article empowers the comptroller to oversee companies’ performance and their compliance with the law from the moment of their registration, emphasizing the importance of not being deleted. Noteworthy recommendations include the necessity of imposing additional penalties on companies that fail to cooperate with the comptroller, enhancing their role in both preventive and punitive oversight. Furthermore, the study emphasizes consolidating the principle of comprehensive oversight to promote corporate governance, control, and early detection.